2011
DOI: 10.1039/c1nr10665a
|View full text |Cite
|
Sign up to set email alerts
|

Strong photo-response in a flip-chip nanowire p-Cu2O/n-ZnO junction

Abstract: Cu(2)O nanoneedles are synthesized on a copper substrate by a simple anodization and reducing ambient annealing protocol. ZnO nanorods are grown on ITO coated glass by a low temperature chemical route. The electronic and photo-response properties of the p-Cu(2)O/n-ZnO flip-chip heterojunction are then studied and analyzed. We show that the I-V characteristic is rectifying and the junction exhibits a good photoresponse (∼120% under 1 V reverse bias) under AM 1.5 (1 Sun) illumination. This nano-heterojunction ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 15 publications
2
42
0
Order By: Relevance
“…Fig. 4,8,10,28,29 Furthermore, a comparison experiment was carried out via switching ZnO and Cu 2 O deposition order on SWNT-based PET. It can be seen that the photoresponsivity, dened as the ratio of the current under the illumination to that under the dark, can reach 520, which is a signicant increase of 3000% compared to the result presented in a recent report.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 4,8,10,28,29 Furthermore, a comparison experiment was carried out via switching ZnO and Cu 2 O deposition order on SWNT-based PET. It can be seen that the photoresponsivity, dened as the ratio of the current under the illumination to that under the dark, can reach 520, which is a signicant increase of 3000% compared to the result presented in a recent report.…”
Section: Resultsmentioning
confidence: 99%
“…However, it requires synthesizing at high temperature, complicated process control, and rigorous conditions. 20 A few studies of the ZnO/Cu 2 O heterojunction have been reported for photovoltaic, 17 photocatalytic, 20,27 and photosensitive 28,29 applications. It is one of the most studied metal oxides for solar cells, [17][18][19] photocatalysts, 20,21 photosensors, 22,23 and photoelectrochemical (PEC) applications, [24][25][26] because of its high optical absorption coefficient, nontoxicity, abundant availability and low production cost.…”
Section: Introductionmentioning
confidence: 99%
“…The property of semiconductor heterostructure dominates the behavior of photoinduced charge carrier, which finally determines the photoelectrochemical response. As is known, a variety of Cu 2 O/ZnO p-n junctions have been applied for enhanced photocatalytic performance and efficient photovoltaic cells due to their controllable electronic structure at interface and good energy band alignment 8 9 10 11 12 13 14 15 16 17 18 19 . ZnO nanomaterials have been extensively studied because of their rather rich morphology world, large excitation binding energy (60 meV), deep level defects and high electron mobility 20 21 22 23 .…”
mentioning
confidence: 99%
“…To further conrm the charge transfer and performance of the proposed tandem PEC cell, a ip-chip method (Fig. 8A) 73 was used in the absence of any sacricial redox species such as water. A light-activated heterojunction diode between C/Cu 2 O NNs and TiO 2Àx NRs can be established with a low turn-on voltage around 0.15 V when these nanostructured electrodes are in intimate contact.…”
Section: Resultsmentioning
confidence: 99%